2001
DOI: 10.1177/089686080102103s36
|View full text |Cite
|
Sign up to set email alerts
|

Lower Malfunction Rate with Self-Locating Catheters

Abstract: Objective We analyzed malfunction rates (obstruction, omental wrapping, displacement) and catheter survival for self-locating catheters as compared with other Tenckhoff catheter designs. Patients and Methods We conducted our survey at two centers, prospectively studying all self-locating catheters implanted from May 1997 to October 2000 and used for peritoneal dialysis (PD). Tenckhoff catheters of other designs used previously in our units were used as the control group. We analyzed removal causes and catheter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…These data may be difficult to interpret as, in some cases, they describe complications (bleeding, leakage, ESI, peritonitis, hernias, or extrusion) that can be managed with peritoneal rest and conservative measures (15)(16)(17)22). Minguela et al removed 20 catheters (3 SLC/17 TC) and described other complications in a ratio of 40/18 (18). The most important article by Di Paolo et al describes 95 SLCs and 65 TCs with complications and 84/46 substitutions (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data may be difficult to interpret as, in some cases, they describe complications (bleeding, leakage, ESI, peritonitis, hernias, or extrusion) that can be managed with peritoneal rest and conservative measures (15)(16)(17)22). Minguela et al removed 20 catheters (3 SLC/17 TC) and described other complications in a ratio of 40/18 (18). The most important article by Di Paolo et al describes 95 SLCs and 65 TCs with complications and 84/46 substitutions (19).…”
Section: Discussionmentioning
confidence: 99%
“…Some prospective studies (3)(4)(5)(6)(7)(8) show mixed results regarding catheter malfunction and survival when comparing catheters with a straight or spiral intraperitoneal segment or with any other device. At the time of writing this study, we were aware of only observational, nonrandomized studies that compare SLCs with CTs, generally double-cuff (15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown improved function, decreased migration, and longer catheter survival with the SLPDC. [9][10][11][12][13][14] However, drawbacks of the SLPDC include the signi cantly increased diameter of the terminal tungsten cylinder compared to the nominal diameter of the catheter precluding the ability to place it percutaneously through small sheaths, its inability to vary the length of the effective catheter, and its restricted application to a straight catheter instead of a coiled catheter.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in the annual peritonitis rate (self‐locating 0.72 ± 1.42, straight 0.95 ± 2.31, coiled 0.65 ± 0.86 episodes annually). There was better catheter survival in the self‐locating group at 1, 2 and 3 years than the coiled or straight groups, respectively (97%, 80%, 75% at 1 years and 96%, 80%, 67% at 3 years) 18 …”
Section: Suggestions For Clinical Carementioning
confidence: 91%